Presença em educação a distância: o caso dos cursos superiores da UAB/IFCE - Schmidlin, Iraci de Oliveira Moraes (2013)
This research is focused on the types of presence and its implications in the context of distance learning. What are the forms to be present in everyday situations, including distance learning, considering the advancement of digital technologies and Internet communications? This issue is discussed taking the Instituto Federal do Ceará (IFCE) and its Diretoria de Educação a Distância (DEaD) as the environment for research and analysis. The undergraduate courses chosen for this case study are offered in the blended learning model via the Universidade Aberta do Brasil (UAB): Tecnologia em Hospitalidade and Licenciatura em Matemática. The research aims to analyse the main types of presence of the student in distance education, and discuss the concept of presence and their interrelations with the concepts of distance, absence, interaction and interactivity in distance education, and describe ways of measuring presence of the student and the tutor used in blended learning model, from the student perspective. The research is mainly based on Michael Moore’s Theory of Transactional Distance, and the types of interaction on the Cesar Coll’s didactic triangle, as well as in the works of Romero Tori, Karla Godoy, Marco Silva, Erving Goffman and Mikhail Bakhtin, among other authors. This case study analyzed qualitatively the results from a questionnaire applied among students of both courses, an in-depth interview conducted with a teacher, and a document analysis of DEaD-IFCE. The results show that the student understands that his presence is assessed through the tutor’s observation to their engagement in the activities. It was also found that the student relates the concept of being present mainly with interaction (especially the student-student interaction), and the sense of belonging to the group (social presence). The social and cognitive presences, beyond the physical presence, were usually in the descriptions made by the students. The results also revealed that the bias towards the physical presence and the paradigms of on-site learning are still very strong in the context UAB/DEaD/IFCE. Although Distance Learning students often need autonomy and flexibility of time and space, they signals in their placements that physical presence in their learning process brings better results.